Optimizing Management Practices for Boosting Creativity and Innovation in Multinational Corporations: Evidence from PZ Cussons Nigeria Plc. - Zekeri Abu; Kayode Muhammed Ibrahim (Jurnal Simki Economic, 2025)
The research focused on optimizing management practices for boosting creativity and innovation in multinational corporations. Rapid technology advancement, shorter product life cycles, dynamic services, and globalisation are becoming increasingly prevalent features of the business environment. The specific objectives were to investigate the role of access to technology on idea conversion rate, analyse digital infrastructure on idea conversion rate and examine the skills development initiatives on the idea conversion rate. Resource-based view theory was adopted for this study. A descriptive survey research design was utilised for the study, and a self-structured questionnaire was used to gather information. The study population was 946 PZ Cussons Nigeria Plc employees and a sample size of 211 was determined using the Raosoft (2004) formula. Multiple linear regression was used to test the hypothesis, and socio-demographic data were analysed using a frequency table and percentage. The result showed a positive correlation of 0.487. The result indicates that access technology has a negative coefficient of -.156 on idea conversion rates, while digital infrastructure and skill development initiatives have positive coefficients of .451 and .574 on idea conversion rates. It was therefore recommended that establishing management rules that are adaptable and sensitive to the ever-changing business landscape is advised for businesses.